The Association of Working Duration with Lung Function and Chest X-Ray Results in Ceramic Industry Workers of Company X, Mabar Medan - Marini Puspita Sari; Amira P Tarigan; Nuryunita Nainggolan; Putri C Eyanoer; Agus Dwi Susanto; Erlangga Samoedro; Caecilia Marliana (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Ceramics industry workers are often exposed to silica materials from ceramics. The aim of this study was to determine the association between silica exposure withlung function test and chest x-ray (CXR) results of the workers. Methods: This was an analytical study with cross-sectional design conducted in the Ceramic Industry X in Mabar, Medan City. The dust level in the work station was measured using Personal Dust Sampler. Lung function was measured by spirometry and CXR was evaluated using the ILO interpretations. Results: About 35 male workers were included as subjects, divided into 3 working stations namely precompression section of 11 subjects (31.4%), compression section of 13 subjects (37.1%) and 11 subjects (31.4%) in the sintering section. Dust levels in each work location are 24.8, 29.2, and 6.11 respectively. Of all subjects, 9 (25.7%) had respiratory symptoms, 21 (60%) had restriction in lung function and 8 (22.8%) had abnormal CXR (6 pneumoconiosis and 2 tuberculosis). There were no association between dust levels with lung function and CXR (P>0.05), but there was a significant correlation between duration of work with lung function. The FEV1 and FVC values of subjects working